The Effect of Digitalization of Banking Services on Consumer Satisfaction - Panjaitan, Chetrin Ruth Caroline; Sianturi, Charles M.; Rajagukguk, Jonson (Golden Ratio of Data in Summary, 2024)
Digitalization services are a banking innovation in providing fast services that can be accessed anytime and anywhere to consumers. Bank BRI Sisimangaraja is one of the banks developing this digitalization service innovation. Consumer satisfaction is the main factor that must be considered by a service provider company, especially banking, to maintain the company's survival. Therefore, in order to achieve consumer satisfaction, digitalization services are carried out well and correctly. The aim of this research is to find out whether the digitalization of banking services has an effect on bank consumer satisfaction. In accordance with research, there are four elements of measuring banking digitalization services that influence consumer satisfaction, namely speed, accuracy, comfort and security. This research uses quantitative research methods with multiple linear regression analysis. The respondents in this research were 120 people who were active customers of Bank BRI Sisimangaraja. The research results obtained from this research show that speed has a significant effect on consumer satisfaction. The size of the regression coefficient is 0.221, meaning that speed influences consumer satisfaction by 0.221 units. Accuracy has a significant effect on consumer satisfaction. The size of the regression coefficient is 0.267, meaning that accuracy influences consumer satisfaction by 0.267 units. Convenience has a significant effect on consumer satisfaction. The size of the regression coefficient is 0.452, meaning that comfort influences consumer satisfaction by 0.452 units. Security has a significant effect on consumer satisfaction. The size of the regression coefficient is 0.710, meaning that security influences consumer satisfaction by 0.710 units. In this way, speed, accuracy, comfort and security have a significant effect simultaneously (together) on the consumer satisfaction variable. Based on the results of the table analysis, the adjusted R square value is 0.479. This means that the influence of service and product quality contributes a joint influence of 47.9% to the consumer satisfaction variable, while the remaining 52.1% is influenced by other variables.